Online volunteering at DigiVol: an innovative crowd-sourcing approach for heritage tourism artefacts preservation - Alony, I.; Haski-Leventhal, D.; Lockstone-Binney, L.; Holmes, Kirsten; Meijs, L.C.P.M. (2020)
Most museums find that the resources required to transform from curators into providers of heritage and cultural tourism exceed those available to them. One way of addressing this challenge is through volunteer programs to assist in heritage tourism artefacts preservation. This article is based on a case study of an innovative crowd-sourcing initiative of integrating on-site and online volunteers for the preservation and documentation of heritage artefacts: the DigiVol program at the Australian Museum, Sydney. This large citizen science volunteer program has digitised an unprecedented portion of the museum’s collections and has been recognised in Australia and internationally as a best practice ‘volunteer digitisation service’ model. Seeking further empirical support for the emerging concept of ‘recruitability’ from the volunteering literature (i.e. the ability of volunteer organisations to recruit and retain volunteers), this research used case study methodology. Based on interviews, focus groups, and document analyses, the article identifies key elements of innovation and effectiveness in DigiVol practices. The article concludes with recommendations for programs wishing to follow best practice and expand their recruitability, to digitise and preserve artefacts, and therefore support science, tourism and education.